Adsorption dynamics and equilibrium studies of nitrate onto various soils - Akosman, Cevdet; Özdemir, Tuba (My University, 2010)
In this study, the adsorption of nitrate onto different kinds of soils (sand, loam and clay) was carried out in a batch system. The adsorption studies of nitrate from aqueous solution onto soil samples were investigated in the range of 25-500 mg L-1 initial nitrate concentrations at the temperatures of 15, 25, 35 and 45 °C. The amount of nitrate adsorbed onto soils increased in the order of clay>loam> sand. The adsorption data are analyzed in terms of adsorption isotherms and thermodynamic parameters. For all soils used, it was found that the adsorption of nitrate was consistent with Freundlich adsorption isotherm. The thermodynamic equilibrium constants (K 0) for adsorption of nitrate onto soils were obtained at different temperatures. The thermodynamic parameters (?H°, ?G°, ?S°) have been calculated for predicting the nature of adsorption. The enthalpies of adsorption for all soil samples are negative indicating the adsorption process is exothermic. © by PSP.
Keywords: Adsorption; Adsorption equilibrium; thermodynamics; Adsorption isotherms; Nitrate; Soil